Weaning age impacts intestinal stabilization of jejunal intraepithelial T lymphocytes and mucosal microbiota in pigs - Jayne E. Wiarda; Hannah R. Watkins; Melissa S. Monson; Christopher L. Anderson; Crystal L. Loving (BMC Veterinary Research)
Abstract Weaning in conventional pig production is a stressful event that involves abrupt dietary and environmental changes, and the post-weaning period is associated with increased incidence of disease and antibiotic use. As a result, there is a growing demand for non-antibiotic practices to enhance health during this phase of production. Current production systems wean piglets at a relatively young age, and it is unclear if age at weaning impacts shifts in intestinal immune populations, particularly intraepithelial T lymphocyte (T-IEL) populations, or bacterial communities, in a comparable timeframe and magnitude. T-IELs reside in the intestinal epithelium and play a role in intestinal integrity and defense. While later weaning may be an approach to minimize the negative impacts of weaning, the impact of age at weaning on T-IEL abundances and function is not clearly understood. Our results indicate pigs weaned at 18–21 days of age (doa; standard weaned, SW), which is consistent with production practices in the United States, had delayed shifts in T-IEL populations when compared to pigs weaned at 25–28 doa (late weaned, LW), which is consistent with practices in the European Union. Specifically, the abundance of induced T-IELs (CD8αβ+ αβ T cells) in the jejunum increased between 0 and 3 days post-weaning (dpw) for the LW group and stabilized, but shifts were delayed until between 3 and 7dpw in the SW group. Concomitant decreases in the abundance of natural T-IEL (γδ T cells) were detected. The structure of jejunal mucosal bacterial communities were comparable between SW and LW pigs at 0dpw, but the SW group had more pronounced shifts from 3 to 7dpw and 7dpw to 14dpw compared to minimal shift in LW group from 7 to 14dpw. Body weight between groups was comparable when adjusted for age. Overall, the bacterial communities of the jejunal mucosa were more stable after weaning in LW than SW pigs, and jejunal T-IEL abundances stabilized more rapidly in the LW group. As T-IELs play a key role in intestinal homeostasis and barrier integrity, the early differences in population abundance may be indicative of functional differences as well.